Assessment of the Profitability of Environmental Activities in Forestry - Танасієва, Марина (Sustainability, 2020)
The paper presents a framework for the financial analysis of the environmental measures (programmes) for forestry enterprises. The indicators of the economic and social e ectiveness of environmental measures are discussed. The prospects for their implementation in the context of sustainable forest management in Ukraine are analysed. The research focuses on the e ectiveness of environmental measures at the level of forestry enterprise. The proposed framework allows for determining the economic and social e ectiveness of environmental measures at the enterprise level. To this end, the net discounted income is used to measure the profitability of environmental measures. The payback period is determined to provide an intuition behind the decision to participate in the environmental measures. The proposed framework allows for improving decision support for the national sustainable forestry development programmes not only at the macro level, but also at the level of enterprises.
Keywords: природоохоронна діяльність; управлінські рішення; математична модель; лісове господарство; доходи